Evaluating Error of Temporal Disaggregation from Daily into Hourly Rainfall using Heytos Model at Sampean Catchments Area - Hidayah, Entin; Anwar, Nadjadji; Edijatno, Edijatno; Iriawan, Nur (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Developing a rainfall-runoff model sufficient to flood prediction hourly rainfall data. Lack of automatic rain gauge for high resolution rainfall in catchment area can be an obstacle for the modeling. Otherwise, the manual rain gauges may spread on all of catchments areas, providing daily rainfall. Daily rainfall disaggregation to hourly rainfall is an innovation to get higher temporal resolution of the rainfall. This paper attempts to evaluate the implementation of rainfall disaggregation model in Sampean Catchments Area using Heytos. The proposed parameter optimation use Moment Performance model that tested by calibrating it with available hourly data. The results of model indicated that only data within five months had good performance. The estimation result showed that relative error total of January, February, August, November, and December was less than one. In case of March, April, May, June, July, September, and October the model could not result respectively to generate model.